PENGEMBANGAN MEDIA REKTISANMORI PADA MATERI PESAN MORAL CERITA NARASI DI KELAS V - Wulan Sari, Rini; Djuanda, Dadan; Dwija Iswara, Prana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop REKTISANMORI (Automatic Correction of Moral Messages) media based on a website of moral message material for narrative stories to help students conclude moral messages in a narrative story. Based on the results of the research, the development of REKTISANMORI (Automatic Correction of Moral Messages) media based on a website of moral message material for narrative stories can be used in the learning process with the category of